Spatial patterns in the understorey shrub genus Psychotria in central Amazonia: Effects of distance and topography - Kinupp, Valdely Ferreira; Magnusson, William Ernest (Journal of Tropical Ecology, 2005)
We evaluated the effects of topography on the distribution of understorey herbs, shrubs and small trees of the pantropical genus Psychotria (Rubiaceae) in a 10 000-ha rain-forest reserve in central Amazonia. As plots were long and thin, and followed altitudinal isoclines, we were able to avoid the trade off between plot size and precision of measurement of topographical variables. The minimum distance between plots (1 km) was sufficient to avoid spatial autocorrelation in topographical variables. However, indices of plot similarity based on species composition were spatially autocorrelated to distances of at least 4 km. Although Multivariate Analysis of Covariance (MANCOVA) indicated significant effects of altitude, slope, and watershed on species composition within plots, topographical variables were generally poor surrogates for species distributions. Differences between eastern and western watersheds within the reserve were not due to distance effects, and most species occurred in both watersheds, indicating that differences in species assemblages between watersheds are determined by ecological factors. Habitat specialization and local density were not clearly associated with rarity. At scales of 1-10 km, both distance and habitat affect the distribution of understorey shrubs of the genus Psychotria, but much of the variation in species abundances remains unexplained. Copyright © 2005 Cambridge University Press.
Keywords: Landscape Ecology; Spatial Analysis; Species Diversity; Topographic Effect; Tropical Forest; Understory; Amazonia; South America; Western Hemisphere; World; Psychotria; Rubiaceae